Pengembangan dan Evaluasi Kurikulum Pendidikan Di Pondok Pesantren Desa Ganjaran Gondanglegi Malang - Yazidul Busthomi (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2020)
Islamic boarding schools in Ganjaran village are Islamic educational institutions. However, curriculum development and evaluation in this boarding school, there is still no data that can be ascertained, so it is interesting to study. Then the researcher raised the title "development and evaluation of educational curricula in the Ganjaran village boarding school". The purpose of this research is to describe the curriculum development and evaluation of Islamic religious curriculum in the Ganjaran village Islamic boarding school. From the results of the study it can be concluded that the development of Islamic religious education curriculum in the hut is by developing curriculum plans with clear objectives, developing curriculum plans in accordance with the characteristics of students, and preparing lesson schedules. Evaluation of the curriculum uses measurement instruments in the form of standardized tests, teacher-made tests, oral tests, and questionnaires.